PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KEPUASAN KERJA DI SMP ISLAM MBAH BOLONG JOMBANG - Septian Ragil Anandita; Saropah Saropah; Wisnu Mahendri (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to determine how the influence of work environment and work motivation on job satisfaction in SMP ISLAM MBAH BOLONG. This research is expected to be used as information and input for school principals and teachers, as well as related parties, as well as the wider community in general regarding the importance of the work environment and motivation on job satisfaction. The type of research used in this research is descriptive quantitative. This study used a sample of 35 respondents. The instrument testing technique in this study is the validity and reliability test, while the data analysis technique uses the classical assumption test, multiple linear regression analysis and the T test and F test hypotheses. The results show that: 1) the work environment has a significant effect on job satisfaction at Islamic Junior High Schools SMP ISLAM MBAH BOLONG 2) Work motivation has no significant effect on job satisfaction at SMP ISLAM MBAH BOLONG. 3) work environment and work motivation simultaneously affect job satisfaction at SMP ISLAM MBAH BOLONG.